Pemetaan Tingkat Bahaya Gempabumi Berbasis Percepatan Getaran Tanah Maksimum Dan Intensitas Gempabumi Di Provinsi Bali - Kelo, Febriyanti Jia; Yuliara, I Made; Setiawan, Yohanes Agus; Sukarasa, I Ketut; Kasmawan, I Gde Antha; Suardana, Putu (Universitas Hamzanwadi, 2023)
The Research has been carried out on the level of earthquake hazard in the Bali region based on maximum ground vibration acceleration (PGA) and earthquake intensity. The data that used in this research were obtained from the BMKG and USGS catalogs. The value of the earthquake hazard level is calculated using the appropriate PGA empirical equation through a correlation test of several empirical equations, namely the Katayama, Mc. Guire, Faccioli, Singh et al, Ambraseys, and Wang & Tao with BMKG observation data.. Based on the correlation test, the Katayama equation (1974) was obtained with the smallest error value of 0.52. The calculation results show that the maximum PGA value ranges from 154-1944 gal and the earthquake intensity ranges from VII to X on the MMI scale with the highest hazard level in the Karangasem, Buleleng, and parts of Jembrana districts.